Clay-pit systems fishfaunistic research in the Middle-Tisza - Demény, Ferenc (Acta Agraria Debreceniensis, 2007)
After the regulation of the Tisza River the chance of successful fish propagation lessened. Natural spooning places in the river almost completely disappeared. The fish have to find an adequate place for their propagation in the flood plain. The period of spooning usually coincides with flooding of the river. At this time fish try to find the flooded shallow places for spooning. These parts mostly include the clay-pits beside dams, which were accidentally established during construction of the dams. At this place the fry can find the necessary food. After decreasing the flood the fingerlings and a part of the spooners are trapped inclay-pits as these latter ones are not connected with the river bed. The clay-pits usually desiccate during the summer. The trapped fish population is eaten by water birds or harvested by the local man population. This means a great loss for reproduction of some fishspecies.Within the framework of the Regional Rehabilitation Program at Nagykörű, supported by the “WWF Hungary” and a “SAPARD project,” these clay-pits became connected with each other in a stretch of 5 km, and they were jointed to the Tisza by a collecting channel. The water level has been regulated by a flood gate so that the water enters the holes during the flood and is released later on in to the water bed.Data on fish were collected from the Nagykörű Whole System, from the Anyita pond and some isolated wholes in Szandaszöllős in 2004 and 2005. First of all fish fry and fingerling were collected and the success of spooning at these places was examined. Fry was harvested by a 60 x 80 cm sized lifting net of 2x3 mm mesh size. In other cases nets used by anglers for catching prey fishes was also used. Data were also collected from local fishermen who participated in saving the fry and fishing of Anyita pond.Of the several thousand caught fish specimens 28 species were identified, and among them 5 protected and 5 economically important species was found. Protected fishes were as follow: gudgeon (Gobio gobio), bitterling (Rhodeus sericeus amarus), weather fish (Misgurnus fossilis), spined loach (Cobitis elongatoides) and tubenosed goby (Proterorhinus marmoratus). Among economically important fishessamples of asp (Aspius aspius), carp (Cyprinus carpio), wels (Silurus glanis), pike (Esox lucius) and pikeperch (Sander lucioperca) were